Nursing Caring Behavior Based on Jean Watson's Theory is Related to Anxiety Levels in Pre-Operative Patients - Nurhayati, Nurhayati; Alfara, Wina; Ritawati, Ritawati; Simeulu, Putro; Taufik, Taufik (Journal Keperawatan, 2024)
Background: Anxiety is the main cause of individual helplessness and accounts for around 15% of global morbidity. More than 28% of people experience anxiety at the age of 18 to old age, where anxiety is usually also associated with psychological conditions and declining individual health so that they must be hospitalized. Caring behavior carried out by nurses makes patients tend to be more comfortable and more optimistic about their recovery. Purpose:  To find out the relationship between caring behavior of nurses based on Jean Watson's theory and the level of anxiety in pre-operative patients. Methods: The type of quantitative research using correlational research design and Cross Sectional Study approach. The population used is pre-operative patients who are in the Regional General Hospital. The sampling method used is non-probability sampling with a sample of 44 respondents. Data collection was carried out through interviews and using the HARS questionnaire. Results: The results of the Chi-Square Test show a p value of 0.004 < 0.05, which means that there is a significant relationship between the caring behavior of nurses based on Jean Watson's theory and the level of pre-operative patient anxiety at the Meuraxa Regional General Hospital, Banda Aceh. Conclusion: There is a significant relationship between caring behavior of nurses based on Jean Watson's theory with the level of preoperative patient anxiety. The more frequently caring behavior is implemented by nurses, the patient's anxiety level will decrease.